Working Toward Integrative Health Equity: Reflections from Acupuncture Implementation Within a Pediatric Primary Care Safety-Net Clinic - Jenifer Matthews; Karen Villanueva; Susan Yee; Ariana Thompson-Lastad (Integrative Medicine Reports, 2022)
Complementary and integrative health (CIH) care is well positioned to provide culturally affirming, patient-centered, and evidence-informed care for vulnerable children and families. Our pediatric primary care clinic has responded to the growing evidence base for CIH in pediatrics and the multiple national calls to action to include nonpharmacologic approaches in the treatment of pain by implementing acupuncture.1,2 Our clinic, a Federally Qualified Health Center (FQHC) in Oakland, CA, USA, serves a multiracial low-income pediatric patient population with 91% of the patients insured by Medicaid. Families served by this clinic face high levels of community trauma and structural violence, contributing to high prevalence of anxiety, depression, post-traumatic stress disorder, and chronic and acute pain conditions.3,4 Within the current biomedical paradigm, treatment options often include pharmaceuticals, lifestyle recommendations, and mental health referrals, but access to these can be fragmented and frustrating for both patients and providers alike. In their call to action, ?Integrative Medicine and the Imperative for Health Justice,? authors Chao and Adler urge us to ?leverage integrative medicine to advance health equity, that is, the attainment of the highest level of health for all people.?5 Acupuncture is one form of CIH that has a growing evidence base for use among children. There is strong interest in the use of pediatric acupuncture in the United States, with evidence for the safety and feasibility of pediatric and adolescent acupuncture as well as acceptability of acupuncture by children.6,7 The benefits of acupuncture for children have been documented in children experiencing chronic pain chemotherapy-associated symptoms, and anxiety, among other conditions.8?10 Widespread implementation of acupuncture has been limited for multiple reasons, including limited or nonexistent insurance reimbursement as well as assumptions that children will be fearful of needles. The term ?acutherapy? was introduced in the clinic to encompass acupuncture, acupressure, and Gua Sha. This term was used due to concern about patients? reactions and negative conditioning to the term ?puncture? and the potential association of an acupuncture needle and treatment being similar to puncture with a hypodermic needle for venipuncture or vaccine administration. Pediatric patients and their families, particularly those who are unfamiliar with this form of care, can be wary when they hear the words, ?puncture? or ?needles,? and language matters with all patients, especially those who have a history of chronic illness or medical trauma. As part of a larger hospital-based interdisciplinary Integrative Medicine Medical Staff Committee, the group?including a physician, licensed acupuncturist/nurse, social worker, and sociologist?collected preliminary data to better understand staff and family priorities, as well as potential barriers to care as acutherapy was implemented in this clinic. Although there are exemplary models of pediatric integrative medicine implementation, these programs are often in academic hospital-based inpatient settings and it can be difficult to translate these experiences to a pediatric primary care safety-net setting.11?13 However, Silver Highfield et al. found that by reducing barriers to access, both pediatric and adult patients in a similar safety-net urban setting utilized acupuncture as part of ongoing primary care.14 To reduce barriers and center family voices in the planning stage of this project, caregivers were surveyed about their current CIH usage and interest, and offered caregiver engagement sessions in multiple languages in the clinic. Over a 3-month period in 2019?2020, families were surveyed in three languages?English, Spanish, and Arabic?about current CIH usage and potential interest in CIH modalities if offered in the clinic, as well as ways to make CIH offerings convenient and accessible. Fifty-nine caregivers completed the survey, and included families broadly reflective of the patients served in clinic* (Table 1).